Pocket companion to Sabiston textbook of surgery - Townsend, Courtney M.; Sabiston, David C. (Philadelphia : Saunders, 2003)
This CD-ROM concentrates on the specific how-to's you need to know in the operating room. A bulleted, outline format makes information easy to access quickly
Handheld software
System requirements : Computer ; Windows 95 and above, Internet connection (Internet Explorer 5.0 minimum), Palm Desktop, ActiveSync, or PC Connect for Cassiopea
System requirements : PDA ; Palm OS (3.5 and above), Windows CE (2.0 and above), or PocketPC
Keywords: Surgical Procedures, Operative -- cd-rom; Perioperative Care -- cd-rom; Surgery -- cd-rom